System of didactic-methodological actions of learning evaluation in professional training - Pozo Vinueza, Mónica Alexandra; Cruz, Miguel Alejandro; Lugo Denis, Dayron; Alonso Jiménez, Lianet (I+ T+ C- Research, Technology and Science, 2017)
In this work a system of didactic-methodological actions of evaluation of the learning in the professional formation is contributed, taking into account the demands of the Contemporary Higher Education in order to contribute to the formative integrality of the professionals. This evaluative construct is distinguished by its practical-professional approach in terms of professional and professional projection. Evaluative actions are intended for each evaluating agent, the ones that design in the short, medium and long term, every time, that make possible the achievement of a process of professional training with quality and efficiency. The objective of the system of proposed actions is to improve the socio-professional projection, through the logic of practical-professional evaluation, to contribute to the formative integrality required in its performance, depending on the career in question. For its elaboration the systemic functional structural method is assumed, characterized by the interrelation between its stages and the sequential logic that is articulated between the specific objectives and actions revealed in each of them, as an expression of their recursion. The effective accomplishment of the actions will allow to assess the level of proximity to the desired state, starting from the considerations about the achieved achievements and the difficulties that have been presented with the instrumentation of each action proposed for the systematization of the formative requirements of the socio-professional projection, From a practical-professional evaluative conception. It is proposed the application of a methodological didactic strategy of practical-professional evaluation, as an expression of a new type of training assignment that facilitates the materialization of the system of actions presented.